Pathological fracture in children with benign bone lesion of the proximal femur managed with LCP Paediatric Hip plate and calcium sulphate as bone substitute - a case series - Sharifudin, Mohd Ariff; Goh, Kian Liang; Mohamed Amin, Mohamed Azril; Awang, Mohd Shukrimi; Abdul Razak, Ardilla Hanim; Taib, Mai Nurul Ashikin (2016)
Objectives:The method of treatment for pathological fractures of proximal femur in children must be able to provide a stable fixation at the same time respect the anatomical peculiarities of the region. This case series demonstrates the use of LCP paediatric hip plate with injectable calcium sulphate (CaSO4) as a treatment option. Materials and Method:Three children aged between 6 to 9 years old presented with pathological fracture Delbet-Colonna type IV following fall. Diagnosis of lesions (2 unicameral bone cyst, 1 fibrous dysplasia) were made pre-operatively by MRI and confirmed on HPE from sample taken intraoperatively. The fractures were fixed using LCP paediatric hip plate 120°. Injectable CaSO4 was inserted through cortical window to fill the bone defect. Results: Acceptable neck-shaft angle was restored and stable fixation achieved in all three cases. No screw inserted through the physis. At 6 weeks following surgery, abundant of callus observed on plain radiograph. Complete union was achieved at 12 weeks. CaSO4 completely resorbed and the original lesions reduced in size by 16 weeks. New bone formations filled in the defect and consolidated. One patient had shortening of 1cm while another had minimal external rotation of 30° on 90° hip flexion. Patients were allowed full weight bearing by then. No abnormal gait observed. Conclusion: Stable fixation with good operative outcomes achieved in treating pathological fractures in the cases. Necessity of obtaining bone graft in the patients was avoided, preventing donor site morbidity and shortened the operative time. Furthermore, conservative treatment with prolonged use of hip spica was not needed.